Urinary tract infection among neonatal sepsis of late-onset in Cipto Mangunkusumo Hospital - Novie Amelia; Idham Amir; Partini P Trihono (Indonesian Pediatric Society, 2005)
Background Urine culture, as part of a full septic work-up forlate-onset neonatal sepsis, was not routinely done in the Neona-tal Ward at Cipto Mangunkusumo Hospital, and as of today, theprevalence of urinary tract infection (UTI) among neonates withlate-onset sepsis remains unknown.Objectives To determine the prevalence and microbiological pat-terns of UTI among late-onset neonatal sepsis in CiptoMangunkusumo Hospital.Methods We conducted a cross-sectional study on all neonatesdiagnosed as suspected late-onset sepsis who underwent sep-sis evaluation between 20 October 2003 – 30 April 2004. Urinespecimens were collected by bladder catheterization for cultureand urinalysis.Results UTI was found in 14.9% (7/47) neonates who under-went urine culture (male: female ratio was 5:2). Six subjectswho had UTI were preterm neonates, Klebsiella pneumoniaewas found in both blood and urine cultures of 1 subject, while theothers showed different microorganisms. Forty-five out of 47subjects, who were suspected of late-onset sepsis, had posi-tive blood cultures. All subjects with UTI had positive bacteriuriafrom Gram-stained specimen.Conclusions The prevalence of UTI among neonates with late-onset sepsis in Cipto Mangunkusumo Hospital was 14.9%. Themicroorganisms most frequently found in urine cultures werePseudomonas sp., Staphylococcus epidermidis, and Klebsiellapneumoniae. Urine culture, urinalysis, and urinary Gram-stainshould be performed as part of sepsis evaluation for late-onsetneonatal sepsis, especially in male and preterm neonates